Science Process Skills in Learning Physics: Is there an influence on learning outcomes? - Eka Nurulia (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
Student science process skills are very important to support student learning. In this study aims to provide information about the effect of science process skills in learning on student learning outcomes. It the study was conducted at Senior High School 1 Toboali using Pre-Experimental Designs with Intact-Group Comparision designs. This study uses material taught in school, namely the topic of effort and energy. The data collection technique using the instrument science process skills and achievement test by dividing the class into two: a control class and experimental class. The data analyzed in descriptive and inferential (Test-T). It analyzes showed that the science process skills have some impact on learning outcomes at a significance level of 0.00 <0.05. Therefore, it is important for teachers to apply the science process skills approach to lengthen student activities during the learning process